Right Anterolateral Thoracotomy for repair of Atrial Septal Defect - صالح, منتجب (Latakia University Journal -Medical Sciences Series, 2023)
Background. A plastic surgical incision can be made in female patients with atrial septal defects via a Right Anterolateral thoracotomy. Methods. A right anterolateral surgical incision was performed on 10 patients during 2018-2020 with an average age of 30 + 10 ; age range: 18-54 years. The defects that repaired include 8 secondary orifice pattern abnormalities, 1 sinus venous pattern, 1 low atrial septal defect, and 4 secondary orifice pattern ( foramen ovale. ( The ascending aorta was used to place an arterial cannula during the cosmetic thoracotomy procedure, and repairs have always been made after cardiac arrest by injection of Cardioplegia solution into the aortic root. Results . No operative deaths or late deaths occurred, nor increased morbidities related directly to thoracotomy. Conclusion. The Right Anterolateral Thoracotomy appears to be a safe and effective alternative to the median thoracotomy for repair of Atrial Septal Defects.